Assessment of the problem-situation by tutors and students on a course of undergraduate experienced in active methodologies - Rodrigo Dornelas; Kelly da Silva; Carla Patrícia Hernadez Alves Ribeiro César; Aline Cabral de Oliveira-Barreto; Raphaela Barroso Guedes-Granzotti (Universidade Estadual Paulista Júlio de Mesquita Filho, 2016)
the objective of this text is compare the assessments of students and tutors about the problems used in a Phonoaudiology course structured in active methodologies. The comparison was performed of formative assessment by 30 students and four tutors of Cycle II of Phonoaudiology course at a public university. 36 problem situations were analyzed using scales from zero (poor) to four (excellent), assigned to evaluate problem situations. The results were analyzed statistically (Kappa coefficient and Mann - Whitney, with a significance level of 5 %). There was no agreement between the evaluations of the problems by students and tutors (Kappa index= 0.0036 ), and that students given higher scores for the issues of problems (mean: 3.7 ) when compared to the tutors (mean: 3.16 ) , although all have assigned good facility for the resolution of problem situations. There was no agreement between the evaluations of problem situations between tutors and students.